Norms of the Russian literary language - Aksionova V. V. (A breakthrough in science: development strategies, 2022)
In the linguistic literature of recent years there are several classifications of the norms of the Russian language. One of the reasons for the allocation of norms is their obligation.
Keywords: литературный язык; Linguistic literature; norms of the Russian language; лингвистическая литература; нормы русского языка